Associations of dispositional forgivingness with facets of well‐being among Colombian adults: A longitudinal outcome‐wide analysis. (17th October 2022) - Cowden, Richard G.; Chen, Zhuo Job; Bechara, Andrea Ortega; Worthington, Everett L.
Abstract : Many studies have reported evidence suggesting that dispositional forgivingness has positive implications for different domains of well‐being. However, relatively few methodologically rigorous studies have been conducted in the Global South, particularly in post‐conflict settings where forgiveness could play an important role in supporting individual well‐being. In this three‐wave cohort study of predominantly young adult Colombians ( n = 1575), we examined the associations of dispositional forgivingness with 20 well‐being outcomes across several domains of well‐being: psychological distress, psychological well‐being, physical health, social well‐being, and character strengths/virtues. Using an outcome‐wide analytic design that included extensive control for potential confounding and reverse causation by adjusting for a range of covariates assessed in Wave 1 (2017), we found that dispositional forgivingness assessed in Wave 2 (2018) was at least modestly associated with improvements in one or more facet of each well‐being domain assessed approximately 1 year later in Wave 3 (2019). Associations tended to be stronger for outcomes in the domains of psychological distress, psychological well‐being, social well‐being, and character strengths/virtues compared to the physical health domain. These longitudinal findings suggest that dispositional forgivingness might promote individual well‐being in societies with a long history of ongoing civil unrest, conflict, and war.